Peningkatan Pengetahuan Tentang Anemia Pada Santriwati Pondok Pesantren Awwaliyah Al-Asiyah - Adhila Fayasari; Isti Istianah (Universitas Binawan, 2023)
Anemia is caused by a deficiency of micronutrients, also known as hidden hunger. Adolescents have a risk of anemia, especially from the frequency of eating, choosing the type of food and the occurrence of puberty. Lack of intake and wrong food choices related to the prevention of anemia in adolescents can be caused by the low knowledge of students regarding this matter. Lack of knowledge about anemia causes the need for iron in the body of adolescents is less and not fulfilled so that anemia can occur in adolescents. Adolescent girls are one of the age groups that are prone to iron deficiency, where their nutritional needs increase because they are still in their infancy. No exception for students in the scope of the boarding school. Boarding schools will provide meals to meet the needs of students and teachers. The provision of dormitory food is generally limited due to financial problems, so there is a possibility that it will not be able to meet the nutritional needs of students. This service aims to increase the knowledge of female students about anemia. The method used is conducting nutrition education, measuring hemoglobin levels, and conducting evaluation analysis to increase the knowledge of female students. This service activity was carried out at the Pesantren Mosque which was attended by 40 female students. The service begins with games to increase enthusiasm and then a pre-test is given. Then the material is given with 3 topics, question and answer, and closed with a post-test and evaluation of activities. The response of the female students was very enthusiastic by asking interesting questions about nutrition and health. The conclusion of the pre-test and post-test results is that there is a significant difference between the level of knowledge before and after nutrition education